2022
DOI: 10.1111/and.14451
|View full text |Cite
|
Sign up to set email alerts
|

Comparative high‐throughput analysis of sperm membrane proteins from crossbred bulls with contrasting fertility

Abstract: The aim of the present study was to identify fertility associated sperm membrane proteins in crossbred bulls. Sperm membrane proteins from high-and low-fertile Holstein Friesian crossbred bulls (n = 3 each) were subjected to high-throughput liquid chromatography-mass spectrometry (LC-MS/MS) for comparative proteomic analy-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…D’Amours et al found the most of the DAPs in HF bull sperm were related to energy metabolism, specifically, the glycolytic pathway member TPI1; adenylate kinase-8, which is involved in ATP production; the transaminase OAT, which enables ATP production through the entry of its product (glutamate) into the tricarboxylic citric acid cycle; and the protein DBIL5, which has been shown to have structural and binding similarity to acetyl CoA binding protein (ACBP) . In addition, Saraf et al found that OXPHOS and the citrate cycle were the most significantly affected pathways in low-fertility crossbred bull sperm …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…D’Amours et al found the most of the DAPs in HF bull sperm were related to energy metabolism, specifically, the glycolytic pathway member TPI1; adenylate kinase-8, which is involved in ATP production; the transaminase OAT, which enables ATP production through the entry of its product (glutamate) into the tricarboxylic citric acid cycle; and the protein DBIL5, which has been shown to have structural and binding similarity to acetyl CoA binding protein (ACBP) . In addition, Saraf et al found that OXPHOS and the citrate cycle were the most significantly affected pathways in low-fertility crossbred bull sperm …”
Section: Discussionmentioning
confidence: 99%
“…22 In addition, Saraf et al found that OXPHOS and the citrate cycle were the most significantly affected pathways in low-fertility crossbred bull sperm. 27 The hallmarks in LF bull spermatozoa are isoforms of the chaperone HSP90 (HSP90AA1 and HSP90B1), members of the chaperonin containing the TCP1 complex, and components of the 20S core proteasome complex (PSMA4 and PSMB4). These results could probably indicate defects in protein folding and proteostasis for this group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, proteomic studies would be beneficial to decipher the roles of sperm proteins on fertility. During the last decade, the proteomic approach helped to find out answers for many of hitherto unanswered questions related to sperm function and bull fertility [17][18][19][20] . Very recently, a preliminary study conducted using 2D-DIGE approach reported that sperm proteins associated with energy metabolism and capacitation were differentially expressed between high-and low-fertile buffalo bulls 21 .…”
mentioning
confidence: 99%